The 2014 Atrial Fibrillation Guidelines Companion: A Practical Approach to the Use of the Canadian Cardiovascular Society Guidelines - Macle, Laurent; Cairns, John A.; Andrade, Jason G.; Mitchell, L. Brent; Nattel, Stanley; Verma, Atul; Verma, Atul; Macle, Laurent; Andrade, Jason; Atzema, Clare; Bell, Alan; Cairns, John A.; et al. (Canadian journal of cardiology, 2015)
The Canadian Cardiovascular Society (CCS) Atrial Fibrillation Guidelines Program has generated a comprehensive series of documents regarding the management of atrial fibrillation (AF) between 2010 and 2014. The guidelines provide evidence-based consensus management recommendations in a broad range of areas. These guidelines have proven useful in informing clinical practice, but often lack detail in specifications related to practical application, particularly for areas in which the evidence base is limited or conflicting. Based on feedback from the community, the CCS Atrial Fibrillation Guidelines Committee has identified a number of areas that require clarification to address commonly asked practical questions related to guidelines application. In the present article a number of such questions are presented and suggestions about how they can be answered are suggested. Among the issues considered are: (1) What duration of AF is clinically significant? (2) How are the risk factors in the CCS Algorithm for selecting anticoagulation therapy derived and defined? (3) How is valvular heart disease defined and how do different forms of valve disease affect the choice of anticoagulant therapy for AF patients? (4) How should we quantify renal dysfunction and how does it affect therapeutic choices? The response to these questions and the underlying logic are provided, along with an indication of future research needed where no specific approach can presently be recommended based on the literature. Entre 2010 et 2014, le programme de Lignes directrices de la Société canadienne de cardiologie (SCC) en matière de fibrillation auriculaire (FA) a permis de créer une série de documents détaillés sur la prise en charge de cette affection. Les lignes directrices contiennent des recommandations consensuelles de prise en charge fondées sur des données probantes dans plusieurs sphères d’application. Bien qu’informatives pour la pratique clinique, les lignes directrices manquent parfois de précision quant aux questions d’ordre pratique, particulièrement lorsque les données probantes sont limitées ou conflictuelles. À la suite de rétroactions fournies par la communauté médicale, le comité des lignes directrices en matière de fibrillation auriculaire a établi un certain nombre de sujets devant être clarifiés pour répondre aux questions d’ordre pratique fréquemment posées sur l’application des lignes directrices. Vous trouverez dans cet article un certain nombre de questions et des pistes de réponses possibles, notamment : 1) Quelle est la durée d’une FA cliniquement significative? 2) Comment les facteurs de risque de l’algorithme de la SCC pour la sélection d’un traitement anticoagulant sont-ils déterminés et définis? 3) Quelle est la définition de la valvulopathie et comment les différentes formes de cette affection influent-elles sur le choix du traitement anticoagulant chez les patients atteints de FA? 4) Comment quantifier la dysfonction rénale et quelle est son incidence sur les choix thérapeutiques? Vous obtiendrez des réponses à toutes ces questions en plus de prendre connaissance de la logique qui les sous-tend. Vous obtiendrez aussi des indications relativement aux études cliniques qui seront nécessaires pour valider les approches qui ne peuvent actuellement être fondées sur des données probantes.